Technology-Enhanced Mathematics Learning: A Systematic Review of Pedagogical Opportunities and Practical Constraints - Dahal, Prem Prasad; Panta, Rudra Kumar (International Research Journal of MMC, 2026)
The use of digital technology in mathematics education has gained significant interest over the past few years with the rapid development of technology and the changing practices in education all around the world. Technology-enhanced learning of mathematics has been increasingly used to enhance conceptual understanding, engagement and problem-solving skills of the students. This study was an attempt to identify and synthesize the pedagogical opportunities of technology enhanced mathematics learning and examine the practical constraints associated with the integration of technology in mathematics education. This research is a systematic review of the studies published between 2020 and 2025 concerning the pedagogical opportunities and practical limitations regarding the use of technology in mathematics education. Following the PRISMA framework, a systematic identification, screening, and analysis of peer-reviewed journal articles were performed. After a rigorous selection process eighteen studies were identified to have met the predefined inclusion criteria, and included in the final review. The selected studies were analyzed with the method of thematic analysis used to identify recurring patterns in the literature and key themes. The results indicated that technology-enhanced mathematics learning provides important pedagogical opportunities such as better conceptual understanding, better student motivation, and development of higher-order thinking skills as well as individualized learning experiences and inclusive education support. However, persistent practical problems were also identified, including insufficient preparedness of teachers, insufficient technological infrastructure, digital inequity, misalignment of curriculum and ethical issues concerning artificial intelligence. The findings in this study conclude that while technology has great potential to transform mathematics education, the effectiveness of technology depends on pedagogical alignment, teacher competence and institutional support. Addressing these constraints is crucial to ensuring sustainable and meaningful integration of technology in mathematics classrooms.